Female cyclists' experiences of saddle sores and their effect on cycling - Burnie, L.; Burt, P.; Lindsay, K.; Heron, N.; Ansdell, P.; Pastorio, E.; Hicks, K. M.; Brown, N. (Frontiers in Sports and Active Living, 2026)
Objectives: The aims of this study are to: (1) understand the type, severity, and experiences of saddle sores in female cyclists, (2) explore the impact on enjoyment, training, and performance, and (3) what prevention or treatment methods female cyclists use, including discussing these issues with their coach, bike fitters, and medical staff. Methods: 20 competitive female cyclists (age 35.1 ± 7.7 years, cycling for 11.9 ± 7.4 years, three elite, seven subelite, and 10 club cyclists) were interviewed using an open-ended, semistructured approach. A thematic analysis was conducted. Results: Saddle sores were highly prevalent in female cyclists and most occurred in the vulva region. The saddle sores were suggested to be attributed to pressure, friction at saddle contact points, and sweat or a combination of all three. The biggest reported impact of saddle sores was that they reduced the enjoyment of cycling. Participants identified risk factors for developing saddle sores and methods of how they attempted to prevent them from occurring. To treat and manage saddle sores, the participants used treatment creams, modified training, and in severe cases, they sought medical treatment or took a break from cycling. The participants reported the process of finding a comfortable saddle and bicycle setup as trial and error, which was long and expensive. Generally, saddle sores are considered a taboo topic, and many participants in this study were reported to have received poor or conflicting advice on this topic. Conclusion: These findings highlight the need for improved education on the prevention and treatment of saddle sores and more research into female-specific bicycle setup and saddle design.